MELODI KEHIDUPAN: ANALISIS PENGARUH LAGU “CHEERS TO YOUTH” SEVENTEEN TERHADAP PENERIMAAN DIRI REMAJA - Alifah Zahra Rahmadia (STKIP Subang, 2025)
This study aims to analyze the influence of the song “Cheers to Youth” by SEVENTEEN on self-acceptance in adolescents through a literature study method. By analyzing various sources that discuss the relationship between music, emotions, and psychological development of adolescents, this study highlights how the lyrics and melody can influence adolescents' attitudes towards themselves. The results of the study show that the song “Cheers to Youth” contains messages that can increase self-confidence, motivate, and help adolescents in the process of accepting their uniqueness and shortcomings. The results of this study prove the importance of music as an effective medium in supporting the emotional and psychological development of adolescents, especially in fostering a strong sense of self-acceptance. This investigation is an important advancement in understanding the ways in which works of art, especially music, can function as transformative instruments for the younger generation.